(untitled) (PHRASIS | Rivista di studi fraseologici e paremiologici, 2017)
In Spanish language there is a wide set of compound utterances with a numerical quantifier: «make a mess of everything», «to kill two birds with one stone», «don’t give a hoot», «to tell everybody/ to tell the whole world», «dressed to kill or dressed up», etc.. The numeral, in the context of a locution, can denote a precise quantity or, mostly, not; In the latter case, the numeral frequently implies a figurative, metaphorical meaning. The lower numbers of the scale, (one, two, three, four) on the one hand, and, the high numbers of the scale in the phraseological code, (one hundred, one thousand, one hundred thousand, one million), on the other, present a stereotyped symbolic value, respectively, of “few” and “large”: «do not give a damn», «two steps», «there is hardly anyone or a soul», etc.; «annoy the hell out of», «a mile a minute», «thanks a million», etc. The symbolic value of these quantifiers seems to be repeated in other languages. Our study focuses on the determination and the analysis of spanish locutions composed by a numeral denoting a symbolic value.